Outcome of Irrigation and Debridement with Topical Antibiotic Delivery Using Antibiotic-Impregnated Calcium Hydroxyapatite for the Management of Periprosthetic Hip Joint Infection - Hiroki Wakabayashi; Masahiro Hasegawa; Yohei Naito; Shine Tone; Akihiro Sudo (MDPI AG, 2023)
We assessed the clinical results of irrigation and debridement (I&D) with antibiotic-impregnated calcium hydroxyapatite (CHA) as a novel antibiotic delivery system for the treatment of prosthetic-joint-associated infection (PJI) after total hip arthroplasty (THA). Thirteen patients (14 hips) treated with I&D for PJI after THA at our institution between 1997 and 2017 were retrospectively evaluated. The study group included four men (five hips) and nine women, with an average age of 66.3 years. Four patients (five hips) had symptoms of infection within less than 3 weeks; however, nine patients had symptoms of infection over 3 weeks. All patients received I&D with antibiotic-impregnated CHA in the surrounding bone. In two hips (two cups and one stem), cup and/or stem revision were performed with re-implantation because of implant loosening. In ten patients (11 hips), vancomycin hydrochloride was impregnated in the CHA. The average duration of follow-up was 8.1 years. Four patients included in this study died of other causes, with an average follow-up of 6.7 years. Eleven of thirteen patients (12 of 14 hips) were successfully treated, and no signs of infection were observed at the latest follow-up. In two patients (two hips) for whom treatment failed, infection was successfully treated with two-stage re-implantation. Both patients had diabetes mellitus and symptoms of infection over 3 weeks. Eighty-six percent of patients were successfully treated. No complications were observed with this antibiotic-impregnated CHA. I&D treatment with antibiotic-impregnated CHA produced a higher rate of success in patients with PJI after THA.